(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2025)
Conventional river assessments often rely on physico-chemical parameters, which cannot fully capture ecological integrity or long-term impacts of human activities. Benthic macroinvertebrates, however, provide reliable bioindicators as they integrate responses to both short-term and cumulative stressors. This study investigated three rivers in Johor, Malaysia of Sungai Mengkibol, Sungai Dengar and Sungai Madek representing different land-use influences including reference conditions, oil palm plantations and logging activities. Eight sampling stations were established, with benthic macroinvertebrates collected using a Surber net and identified to family or genus level where possible. Four ecological indices were calculated using Shannon-Wiener Diversity Index, Simpson’s Dominance Index, Margalef Richness Index, and Hill’s Evenness Index that purposely to evaluate river health. Threshold values were developed by comparing reference and impaired stations, leading to the establishment of a Recommended Ecological Index for River Health Assessment. Results showed that healthy rivers consistently displayed high diversity (>1.8), high richness (>2.0), low dominance (<0.2), and strong evenness (>0.8), reflecting balanced and resilient communities. In contrast, impaired rivers exposed to anthropogenic pressures recorded low diversity and richness, high dominance, and poor evenness. The proposed framework sets out clear ecological thresholds to help categorize rivers as healthy, slightly unhealthy, or polluted. This is a significant step, as it’s the first time we’re developing reference values for Malaysian rivers using macroinvertebrate indices. The findings emphasize how innovative and practical benthic macroinvertebrate-based biomonitoring can be cost-effective and meaningful from an ecological standpoint. By using these indices, we can strengthen our national river management strategies and promote evidence-based approaches to preserving our tropical freshwater ecosystems.